Enhancement the Osseo Integration Properties of Polymer for Human Body Implants - Rasheed, Dhurgham Majid; Hamdi, Dunya Abdulsahib (Al-Nahrain Journal for Engineering Sciences, 2020)
In this research, polymer polymethyl methacrylate PMMA composite with nano ceramic Zr and HAp material were used to manufacture one part of the implant system (femoral ball head of hip implant). Three set of hybrid materials were fabricated and tested for this study; the first mixtures which contains 100% (PMMA), the second mixtures which contains (90% (PMMA) + 8% (Zr) + 2% (HAp)), and the third mixtures which contains (80% (PMMA) + 18% (Zr) + 2% (HAp)) were investigated. The mechanical properties for these mixtures increased with the increasing of nano ceramic concentration (Zr and HAp) composite material in the polymer compared to pure polymer PMMA sample. However, an increase in the concentration of Zr from 8% to 18% content cause a considerable decrease of the hardness where a drop of homogeneity in Zr- matrix PMMA contact occurred, V Hardness value are (68 ,80 and 70) Kg.mm for three mixture respectively. The wear test was in agreement with results of the hardness test. The weight loss of the above samples of the wear test were (0.041, 0.035 and 0.037) respectively. According to mechanical properties, the best sample contains (90% (PMMA) + 8% (Zr) + 2% (HAp)). The Scanning electron microscopy resolute showed the particles forming semi-continuous network along grain boundaries polymer for second sample mixtures containing (90% (PMMA) + 8% (Zr) + 2% (HAp)), provides a low atomic packing and high energy. This will make the grain boundaries more reactive and strengthen mechanical performance. The Optical microscopy, Scanning electron microscopy and Xray spectroscopy analysis for In vitro test using SBF shows the growth of HAp layer with an increase in concentration of Ca and P elements formed on the surface of the second sample. This display of good results is a proof of the biocompatibility of the polymer sample.